'Hold that Pose!' Photography and kabuki in Kitano Takeshi's Kikujiro. Issue 4 (1st October 2016) - Hutchinson, Rachael
Abstract: This article examines Kitano Takeshi's film Kikujiro ( Kikujirō no Natsu, 1999) from two directions: first, as an as an experiment in moving versus still photography, and second, as an exploration of time, memory and Japanese identity. I argue that it is in Kitano's cinematic use of elements from the kabuki drama that the two aspects come together. Kitano plays upon the conventions of both kabuki and film media to highlight the significance of the 'still shot' as it functions in human memory. By presenting moments of the story in the format of a child's photograph album, Kitano is able to explore ideas of 'adult' and 'child' as equally arbitrary constructions. Throughout Kikujiro, Kitano draws on a rich tradition of film, drama and television convention in order to explore the idea of where identity comes from – does it come from the past, the present, or do we make it up ourselves? Kitano places emphasis on the still mie pose to heighten emotion and draw attention to the present moment. By contrasting this method against that of photography, Kitano juxtaposes past and present modes of expression, enabling him to interrogate notions of time and the supposed timelessness of art. Finally, Kitano's critical use of the past locates identity not in some distant, unobtainable myth of the nation, but in the lived experience of each individual as a human being.